Bioprinted osteon-like scaffolds enhance in vivo neovascularization. (28th March 2019) - Piard, Charlotte; Baker, Hannah; Kamalitdinov, Timur; Fisher, John
Abstract: Bone tissue engineers are facing a daunting challenge when attempting to fabricate bigger constructs intended for use in the treatment of large bone defects, which is the vascularization of the graft. Cell-based approaches and, in particular, the use of in vitro coculture of human umbilical vein endothelial cells (HUVECs) and human mesenchymal stem cells (hMSCs) has been one of the most explored options. We present in this paper an alternative method to mimic the spatial pattern of HUVECs and hMSCs found in native osteons based on the use of extrusion-based 3D bioprinting (3DP). We developed a 3DP biphasic osteon-like scaffold, containing two separate osteogenic and vasculogenic cell populations encapsulated in a fibrin bioink in order to improve neovascularization. To this end, we optimized the fibrin bioink to improve the resolution of printed strands and ensure a reproducible printing process; the influence of printing parameters on extruded strand diameter and cell survival was also investigated. The mechanical strength of the construct was improved by co-printing the fibrin bioink along a supporting PCL carrier scaffold. Compressive mechanical testing showed improved mechanical properties with an average compressive modulus of 131 ± 23 MPa, which falls in the range of cortical bone. HUVEC and hMSC laden fibrin hydrogels were printed in osteon-like patterns and cultured in vitro . A significant increase in gene expression of angiogenic markers was observed for the biomimetic scaffolds. Finally, biphasic scaffolds were implanted subcutaneously in rats. Histological analysis of explanted scaffolds showed a significant increase in the number of blood vessels per area in the 3D printed osteon-like scaffolds. The utilization of these scaffolds in constructing biomimetic osteons for bone regeneration demonstrated a promising capacity to improve neovascularization of the construct. These results indicates that proper cell orientation and scaffold design could play a critical role in neovascularization.